A multiplexed high‐resolution imaging spectrometer for resonant inelastic soft X‐ray scattering spectroscopy. (2nd June 2014) - Warwick, Tony; Chuang, Yi‐De; Voronov, Dmitriy L.; Padmore, Howard A.
<x xml:space="preserve">Abstract</x> The optical design of a two‐dimensional imaging soft X‐ray spectrometer is described. A monochromator will produce a dispersed spectrum in a narrow vertical illuminated stripe (∼2 µm wide by ∼2 mm tall) on a sample. The spectrometer will use inelastically scattered X‐rays to image the extended field on the sample in the incident photon energy direction (vertical), resolving the incident photon energy. At the same time it will image and disperse the scattered photons in the orthogonal (horizontal) direction, resolving the scattered photon energy. The principal challenge is to design a system that images from the flat‐field illumination of the sample to the flat field of the detector and to achieve sufficiently high spectral resolution. This spectrometer provides a completely parallel resonant inelastic X‐ray scattering measurement at high spectral resolution (∼30000) over the energy bandwidth (∼5 eV) of a soft X‐ray absorption resonance.